Indigo Naturalis Alleviates Dextran Sulfate Sodium-Induced Colitis in Rats via Altering Gut Microbiota - Sun, Zhongmei; Li, Junxiang; Dai, Yi; Wang, Wenting; Shi, Rui; Wang, Zhibin; Ding, Panghua; Lu, Qiongqiong; Jiang, Hui; Pei, Wenjing; Zhao, Xingjie; Guo, Yi; et al. (Frontiers in Microbiology, 2020)
Ulcerative colitis is a gastrointestinal disorder intricately associated with intestinal dysbiosis, but effective treatments are currently limited. Indigo naturalis, a traditional Chinese medicine derived from indigo plants, has been widely used in the treatment of ulcerative colitis. However, the specific mechanisms have not yet been identified. Accordingly, in this study, we evaluated the effects and mechanisms of indigo naturalis on dextran sulfate sodium (DSS)-induced colitis in rats. Our results showed that indigo naturalis potently alleviated DSS-induced colitis in rats, and reversed DSS-induced intestinal dysbiosis using bacterial 16S rRNA amplicon sequencing. The protective effects of indigo naturalis were gut microbiota dependent, as demonstrated by antibiotic treatments and fecal microbiota transplantation. Depletion of the gut microbiota through a combination of antibiotic treatments blocked the anti-inflammatory effect of indigo naturalis on the DSS-induced colitis, and the recipients of the gut microbiota from indigo naturalis-treated rats displayed a significantly attenuated intestinal inflammation, which was actively responsive to therapeutic interventions with indigo naturalis. Notably, supplement with indigo naturalis greatly increased the levels of feces butyrate, which was positively correlated with the relative abundances of Ruminococcus_1 and Butyricicoccus. We further showed that indigo naturalis-dependent attenuation of colitis was associated with elevated expression of short-chain fatty acid-associated receptors GPR41 and GPR43. Collectively, these results suggested that indigo naturalis alleviates DSS-induced colitis in rats through a mechanism of the microbiota-butyrate axis, particularly alterations in Ruminococcus_1 and Butyricicoccus abundances, and target-specific microbial species may have unique therapeutic promise for ulcerative colitis.